Meaningful Work and Psychological Empowerment as Predictors of Employee Performance in the Oil and Gas Industry - โกสิงห์ ยุทธชัย; บุณยะประพันธ์ เบญจวรรณ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research are: 1) to study the levels of meaningful work, psychological empowerment, and job performance among employees in the oil and gas industry; 2) to study the relationship between meaningful work and job performance; 3) to study the relationship between psychological empowerment and job performance; and 4) to predict job performance using meaningful work and psychological empowerment. The sample consisted of 369 operational-level employees working in the oil and gas industry. The research instrument was a questionnaire with a 5-point Likert scale. The data were analyzed using frequency, percentage, mean, standard deviation, Pearson’s correlation coefficient, and multiple regression analysis. The results revealed that meaningful work (x̄= 4.31), psychological empowerment (x̄= 4.32), and job performance (x̄= 4.29) were all at high levels. Meaningful work demonstrated a very strong positive relationship with job performance (r = .909, p < .01), while psychological empowerment also showed a very strong positive relationship with job performance (r = .892, p < .01). Furthermore, meaningful work and psychological empowerment jointly and significantly predicted job performance among employees in the oil and gas industry, accounting for 84.40% of the variance in job performance (R2 = .844).